Design of an intelligent sensor network for solar panels - Tan, Andy Weng Kiat. (2010)
Energy industry observers have considered solar energy as an alternative and practical source of energy generation. It is predicted that the world will undergo a major transition in energy sources over the next few decades and clearly, solar is one of the popular energy sources.